INTERACTIVE LEARNING MEDIA DEVELOPMENT TO ENCOURAGE THE STUDENT'S MOTIVATION ON MONETARY ECONOMICS - Puspitasari, Inda Fresti; Aisyah, Siti; Setyowati, Eni; Atfinia, Neiska Syifa (Jurnal Pendidikan Ilmu Sosial, 2024)
In this rapidly advancing digital era, every lecturer or teacher must innovate their learning media. Students in this era, often referred to as Gen Z, are highly familiar with technological advancements, making it necessary for the teaching methods to be adapted so that the material being delivered can be effectively understood and well received by the students. This study aims to develop learning media in the form of an interactive e-book using Lectora Inspire software for the Money Demand and Money Supply topics in the Monetary Economics subject using the Learning Cycle 7E method which requires the students to actively participate in the learning activity. The feasibility test of interactive learning media is based on validation assessment from material experts, linguists, practitioners (lecturers), and students in the Monetary Economics course. The type of research uses a development method (Research and Development) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results of this study indicate that the interactive e-book using Lectora software is very suitable as learning media in monetary economics courses and it is proven toenhance student motivation to learn the subject and increase students' understanding of the money demand and money supply materials in the Monetary Economics course.